THE APPLICATION OF BEHAVIOURAL ARCHITECTURE PRINCIPLES TO SUPPORT THE EFFECTIVENESS OF DRUG REHABILITATION FACILITIES IN NORTH SUMATRA, INDONESIA - Lolyta Monalisa Glendys Sitorus; Hajar Suwantoro (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Drug addiction in North Sumatra remains a critical public health and social issue, characterized by increasing numbers of users and limited rehabilitation facilities. Beyond physical and psychological challenges, social stigma significantly affects patients’ willingness to undergo rehabilitation and influences recovery outcomes. The built environment plays an essential role in shaping human Behaviour, emotional responses, and social interaction during rehabilitation recovery. This study aims to examine how behavioural architecture principles can support the effectiveness of drug rehabilitation facilities. A qualitative descriptive method with a design-based approach is employed. Data were collected through literature review and semi-structured interviews with the National Narcotics Board (BNN/Badan Narkotika Nasional) of Medan. The analysis focuses on the relationship between spatial design and patient behaviour, including movement patterns, emotional regulation, territoriality, and social interaction. The findings indicate that the application of behavioural architecture through spatial zoning, environmental stimulus control, socio-spatial interaction settings, and territorial organization can positively influence patient behaviour, reduce stress, enhance emotional stability, and improve participation in therapeutic programs. The study concludes that behavioural architecture functions as a therapeutic design strategy that supports the effectiveness of drug rehabilitation environments.